Hemorrhagic Adrenal Mass: A Rare Presentation of Primary Adrenal Choriocarcinoma - Tuong Phan; John Spencer Lane; Udit Naik; Jeffrey Chen (Annals of Internal Medicine: Clinical Cases)
Choriocarcinoma comprises less than 5% of all germ cell tumors in men, and primary extragonadal manifestation in the adrenal glands is a subset of that low percentage. Primary adrenal choriocarcinoma is a rare yet devastating diagnosis, with few cases reported in men. Delays in diagnosis can lead to increased morbidity and mortality given choriocarcinoma's aggressive growth; therefore, clinicians must recognize this clinical entity and consider it part of the differential diagnosis of a mass in the adrenals, lung, gastrointestinal tract, or brain, and expedite treatment if index of suspicion is high.